Răspuns :
Salut,
[tex]a_{n+1}=(n+1)^2-(n+1)=n^2+2n+1-n-1=n^2+n,\ deci\ a_{n+1}=n^2+n.\\a_{n+1}-a_n=n^2+n-n^2+n=2n\geqslant 0,\ deci\ a_{n+1}-a_n\geqslant 0,\ adic\breve{a}\ a_{n+1}\geqslant a_n.[/tex]
Asta înseamnă că șirul din enunț este crescător.
Green eyes.
[tex]a_{n+1}=(n+1)^2-(n+1)=n^2+2n+1-n-1=n^2+n,\ deci\ a_{n+1}=n^2+n.\\a_{n+1}-a_n=n^2+n-n^2+n=2n\geqslant 0,\ deci\ a_{n+1}-a_n\geqslant 0,\ adic\breve{a}\ a_{n+1}\geqslant a_n.[/tex]
Asta înseamnă că șirul din enunț este crescător.
Green eyes.